2006
DOI: 10.1590/s1415-43662006000100022
|View full text |Cite
|
Sign up to set email alerts
|

Influência do conteúdo de umidade de colheita e temperatura de secagem na qualidade do feijão

Abstract: Apesar dos avanços, a produção brasileira de feijão sofre perdas consideráveis, até chegar ao consumidor, razão por que se objetivou, com este trabalho, avaliar a qualidade do feijão colhido com diferentes conteúdos de água e secados em diferentes temperaturas do ar, em um secador de camada delgada. Após a limpeza e secagem, os grãos foram expurgados e, em seguida, acondicionados em recipientes metálicos e mantidos em condições de laboratório, durante o período de 90 dias. A avaliação da qualidade foi realizad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
6

Year Published

2009
2009
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 2 publications
0
6
0
6
Order By: Relevance
“…Dessa forma, a alteração na coloração de produtos agrícolas é um atributo de qualidade facilmente identificável (FARONI et al, 2006).…”
Section: Introductionunclassified
“…Dessa forma, a alteração na coloração de produtos agrícolas é um atributo de qualidade facilmente identificável (FARONI et al, 2006).…”
Section: Introductionunclassified
“…These results indicate that the loss of integrity of the components of the membrane was caused by drying at temperatures above 40 ºC, associated to the prolonged storage, since, according to Marcos-Filho (2015), the electrical conductivity test expresses the degree of disorganization of the cell membranes, since the higher their integrity, the greater will be their capacity not to allow leaching and ions from its interior to the soaking solution. However, the integrity may usually be compromised by some factors, such as by the drying air temperature and the storage time, as observed for bean seeds (Faroni et al, 2006), jatropha seeds (Ullmann et al, 2010), adzuki bean seeds (Resende et al, 2012;Almeida et al, 2013), soy seeds (Smaniotto et al, 2014) and saccharine sorghum seeds (Ullmann et al, 2015), whose results related to the electrical conductivity also showed damages occurred on the cellular membranes of the seeds submitted to temperatures above 40 ºC and storage periods of over 100 days.…”
Section: Resultsmentioning
confidence: 99%
“…Resultados semelhantes foram observados por FARONI et al (2006), que observaram aumento linear da condutividade elétrica da solução que contém as sementes de feijão com o tempo de armazenamento. SOUZA et al (2002) concluíram que o período de armazenamento do feijão por 180 dias não influenciou na queda da percentagem de germinação das sementes, quando essas foram colhidas mecanicamente.…”
Section: Electrical Conductivity Estimation (Ec) Of Bean Seeds Depenunclassified